Perceptions of nursing students regarding responsible use of social media in the Eastern Cape - Thando Nyangeni; Suzette du Rand; Dalena van Rooyen (AOSIS, 2015)
Background: Social media have become a popular communication system that has transformed communication from the traditional to the Web-based model. Because social media use has no limitations to place and time, it is now used extensively at clinical facilities. Social media useis becoming a popular activity amongst students at Nursing Education Institutions (NEI) in South Africa. However, lack of accountability and unethical use of social media by nursing students in South Africa has been reported. Objectives: The aim of the study was to explore and describe the perceptions of nursing students regarding responsible use of social media. Methods: A qualitative, descriptive, explorative and contextual research design was used to explore and describe the perceptions of nursing students regarding the responsible use of social media. Twelve nursing students registered for the undergraduate nursing degree were purposely selected and interviewed individually using a semi-structured interview method. Results: The results of this research study demonstrate that nursing students use socialmedia irresponsibly. Nursing students experience blurred boundaries between personal and professional lines and lack accountability when using social media. Conclusion: The extensive use of social media in the clinical environment, by healthcare students, requires a joint effort by Nursing Education Institutions and healthcare facilities to ensure that social media are used in an ethically acceptable manner. The implementation of the recommendations of this research study could positively influence legally and ethically acceptable use of social media at healthcare facilities.